Porvenir. The Cuban strategy to fight Covid-19 and a reflection on the social repercussions of Covid-19 - Portundo, Lixandra (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
This video is an adaptation of the article published in issue 10 of the magazine "Comparative Cultural Studies. European and Latin American Perspective ". It analyzes Cuban government and multidisciplinary strategy to preserve human lives and avoid medical collapse. The Soberana 01 and Soberana 02 vaccines are currently undergoing clinical trials and are recognized by the WHO. In addition to the reference to the situation in Cuba, the work invites an objective reflection on the impact of Covid-19 on a global level on people from an economic, social and political point of view, and allows us to rethink a series of strategies that highlight the recognition of the human being, of his empathy, and of the inevitable social inequalities caused by the pandemic. In addition, emphasis is placed on the possibilities to be implemented to fill the social cracks caused by the coronavirus, through the implementation of a thought aimed at human and social understanding of the phenomenon.